Preparation of titanium dioxide nanotube arrays on titanium mesh by anodization in (NH4)2SO4/NH4F electrolyte. Issue 11 (4th May 2012) - Zeng, Q.‐Y.; Xi, M.; Xu, W.; Li, X.‐J.
Abstract The self‐organized titanium dioxide (TiO2) nanotube arrays on titanium mesh were prepared by electrochemical anodization with the neutral electrolyte containing ammonium sulfate and ammonium fluoride in a two‐electrode electrochemical cell. The effects of the fluoride ion concentration, the anodic potential, and the oxidation time on the formation of the titanium dioxide nanostructures on titanium mesh with complex geometry were investigated. The anodized titanium mesh was characterized by field emission scanning electron microscope and in situ high temperature X‐ray diffraction. The results show that the titanium dioxide nanotube arrays are grown in a radially outward direction around the titanium wire. The optimized anodization condition for preparing titanium dioxide nanotube arrays with superior architecture on the titanium mesh is 0.5 wt% of ammonium fluoride, 20 V of applied potential, and 20 min of oxidation time. The amorphous titanium dioxide nanotubes on titanium mesh turn to anatase phase at 400 °C and further to rutile phase at 650 °C.